Effect of the sodium reduction and smoking system on quality and safety of smoked salmon (Salmo salar). (September 2020) - Muñoz, Israel; Guàrdia, Maria Dolors; Arnau, Jacint; Dalgaard, Paw; Bover, Sara; Fernandes, José O.; Monteiro, Carolina; Cunha, Sara C.; Gonçalves, Amparo; Nunes, Maria Leonor; Oliveira, Helena
Abstract: Excessive sodium (Na) intake has been associated with high blood pressure and cardiovascular diseases. Therefore, sodium reduction is a public health challenge worldwide. The aim of this study was to develop smoked salmon with a reduced Na content. Sodium chloride (NaCl) was replaced by potassium chloride (KCl) at 25% and 50% (molar replacement) and studied in combination with two smoking procedures (natural wood and liquid smoke) as well as two smoking temperatures (18-19 °C or 56 °C). Smoked salmon samples were characterized by physicochemical, sensory and microbiological analyses. No major differences were observed regarding physicochemical properties in the studied treatments. Smoked samples with 50% of NaCl replaced by KCl were slightly more bitter than those with 25% whereas samples with 25% of replacement did not show differences to those with non-reduced Na content (5 g of added NaCl per 100 g of salmon). Molar Na:K ratio decreased from 4, 3 in controls to 1, 4 and 0, 6 in samples with a NaCl reduction level of 25% and 50% respectively. Microbiological assessment indicates that 2-week shelf-life would be appropriate and safe in terms of accomplishment of the EU regulation, taking into account foreseeable storage temperatures (up to 8 °C). Thus, it is possible to achieve a reduction of 25–50% of NaCl in smoked salmon by replacing NaCl by KCl and considerer this product as a "source" of K. Highlights: 25–50% NaCl replacement by KCl was investigated for natural and liquid smoking procedures at 18–19 and 56 °C. No sensory differences were observed for 25% NaCl replacement by KCl in the four smoking treatments. 50% NaCl replacement by KCl resulted in a slightly more bitter product in all the smoking treatments. Salmon with KCl substitution had a 2 week shelf-life when stored in refrigeration. Salmon with KCl substitution could be a "source" of K and Salmon with KCl substitution could be a "reduced salt content" product.